Transforming disadvantages into advantages: developing-country MNEs in the least developed countries - Cuervo-Cazurra, Alvaro; Genc, Mehmet (Journal of International Business Studies, 2008)
We analyze the advantages and disadvantages of developing-country multinational enterprises (MNEs) in comparison with developed-country MNEs. Developing-country MNEs tend to be less competitive than their developed-country counterparts, partly because they suffer the disadvantage of operating in home countries with underdeveloped institutions. We argue that this disadvantage can become an advantage when both types of MNE operate in countries with “difficult” governance conditions, because developing-country MNEs are used to operating in such conditions. The empirical analysis shows that, although developing-country MNEs rarely appear among the largest MNEs in the world, they are more prevalent among the largest foreign firms in the least developed countries (LDCs), especially in LDCs with poorer regulatory quality and lower control of corruption.